Dampak Rill Implementasi Status Otonomi Khusus Di Provinsi Papua, Indonesia: Kajian Hukum Perspektif Good Governance - Ayunda, Rahmi (Program Studi Ilmu Hukum Fakultas Hukum dan Ilmu Sosial Universitas Pendidikan Ganesha Singaraja, 2021)
The reforms that have occurred in Indonesia have changed the joints of the life of the nation and state. One of them is changing the centralistic system of government. The demand for reforms related to the broadest possible implementation of regional autonomy is the beginning of the implementation of the decentralization principle in Indonesia. This principle can be reflected in the presence of the Special Autonomy policy, one of which is in Papua Province. This research uses a normative legal research method with a statutory approach. The results of this research show that the stipulation of special autonomy status for Papua Province is legally based on Law Number 21 of 2001 concerning Special Autonomy for Papua Province. This law is an attempt by the central government to develop Papua to be the same as other regions. There are many specializations and special rights that the Papuan people have obtained through the determination of this status, but they are still not being implemented in real terms in the field. This is due to government inconsistencies, especially when viewed from a good governance perspective. Good governance in the principle of participation in Papua has not been implemented properly because of the existence of considerable power as a cultural representation which has not fully represented the Papuan people so that many rights and opinions and voices of the Papuan people have not been implemented.